2021
DOI: 10.3389/fpls.2021.657960
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Karrikins Receptor Gene Sapium sebiferum KAI2 Promotes the Cold Stress Tolerance via Regulating the Redox Homeostasis in Arabidopsis thaliana

Abstract: KARRIKINS INSENSITIVE2 (KAI2) is the receptor gene for karrikins, recently found to be involved in seed germination, hypocotyl development, and the alleviation of salinity and osmotic stresses. Nevertheless, whether KAI2 could regulate cold tolerance remains elusive. In the present study, we identified that Arabidopsis mutants of KAI2 had a high mortality rate, while overexpression of, a bioenergy plant, Sapium sebiferum KAI2 (SsKAI2) significantly recovered the plants after cold stress. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…In contrast, after chilling for 72 h, strong ROS accumulation was only observed in WT plants, whereas feeble levels of ROS were detected in ospin9 mutants ( Figure 7B ). The antioxidant enzyme system, such as SOD, CAT, and POD, has been proved to function in quenching ROS under various adverse conditions ( Jaleel et al, 2009 ; Shah et al, 2021 ; Song et al, 2021 ). We then analyzed the activity of these three enzymes under normal and chilling conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, after chilling for 72 h, strong ROS accumulation was only observed in WT plants, whereas feeble levels of ROS were detected in ospin9 mutants ( Figure 7B ). The antioxidant enzyme system, such as SOD, CAT, and POD, has been proved to function in quenching ROS under various adverse conditions ( Jaleel et al, 2009 ; Shah et al, 2021 ; Song et al, 2021 ). We then analyzed the activity of these three enzymes under normal and chilling conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, particular focus has been given to understanding the multifunctional roles of soluble sugars in regulating cold tolerance (Hoermiller et al., 2017; Nägele & Heyer, 2013). Increases in glucose and sucrose have been reported to improve cold stress tolerance in tomato (Liu et al., 2020), and increased levels of total soluble sugars also promoted cold stress tolerance in Arabidopsis thaliana (Shah et al., 2021). Here, soluble sugars, including glucose, galactose, sorbitol, and sucrose, also increased significantly in MdMRLK2 ‐OE apple plants during cold treatment (Figure 3a–d).…”
Section: Discussionmentioning
confidence: 99%
“…Karrikin, which is one component of the plant-derived smoke solution [ 18 ], regulated tolerance to abiotic stresses such as drought [ 19 ] and cold [ 20 ] in Arabidopsis thaliana as well as salt [ 21 ] and cadmium [ 22 ] in oil plant. Furthermore, it was reported that the plant-derived smoke solution enhanced soybean growth under flooding [ 13 ] and after flooding [ 12 ].…”
Section: Discussionmentioning
confidence: 99%